Template‐Enabled Biofabrication of Thick 3D Tissues with Patterned Perfusable Macrochannels. Issue 7 (12th January 2022) - Davoodi, Elham; Montazerian, Hossein; Zhianmanesh, Masoud; Abbasgholizadeh, Reza; Haghniaz, Reihaneh; Baidya, Avijit; Pourmohammadali, Homeyra; Annabi, Nasim; Weiss, Paul S.; Toyserkani, Ehsan; Khademhosseini, Ali
Abstract: Interconnected pathways in 3D bioartificial organs are essential to retaining cell activity in thick functional 3D tissues. 3D bioprinting methods have been widely explored in biofabrication of functionally patterned tissues; however, these methods are costly and confined to thin tissue layers due to poor control of low‐viscosity bioinks. Here, cell‐laden hydrogels that could be precisely patterned via water‐soluble gelatin templates are constructed by economical extrusion 3D printed plastic templates. Tortuous co‐continuous plastic networks, designed based on triply periodic minimal surfaces (TPMS), serve as a sacrificial pattern to shape the secondary sacrificial gelatin templates. These templates are eventually used to form cell‐encapsulated gelatin methacryloyl (GelMA) hydrogel scaffolds patterned with the complex interconnected pathways. The proposed fabrication process is compatible with photo‐crosslinkable hydrogels wherein prepolymer casting enables incorporation of high cell populations with high viability. The cell‐laden hydrogel constructs are characterized by robust mechanical behavior. In vivo studies demonstrate a superior cell ingrowth into the highly permeable constructs compared to the bulk hydrogels. Perfusable complex interconnected networks within cell‐encapsulated hydrogels may assist in engineering thick and functional tissue constructs through the permeable internal channels for efficient cellular activities in vivo. Abstract : A biocompatible, economic, and robust biofabrication process is developed to form complex shapes and internal perfusable channels in multilayered thick tissue constructs made from extracellular matrix mimicking soft hydrogels (i.e., gelatin methacryloyl, GelMA). Cell‐laden GelMA hydrogels with interconnected pores demonstrate excellent mechanical tunability and support cell function in vitro and in vivo.